2008
DOI: 10.1002/art.23407
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of toll‐like receptor 7 for pristane‐induced production of autoantibodies and development of murine lupus nephritis

Abstract: Objective. The detection of high titers of antibodies against small nuclear ribonucleoproteins (snRNP) is a diagnostic finding in patients in whom systemic lupus erythematosus (SLE) is suspected. Endogenous RNA molecules within snRNP trigger Toll-like receptor 7 (TLR-7) activation in B cells and dendritic cells, leading to anti-snRNP antibody production, which is associated with the development of immune complex nephritis in SLE. The purpose of this study was to investigate the role of TLR-7 in anti-snRNP anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 29 publications
5
112
0
1
Order By: Relevance
“…STING-deficient MRL/lpr mice develop a dramatically accelerated disease profile characterized by the expansion and activation of both the lymphoid and myeloid compartments, increased numbers of type I IFN-producing cells, elevated autoantibody titers, and a shorter lifespan. Similar to our findings in the MRL/lpr model, STING deficiency exacerbated TMPD-induced inflammation, a condition also associated with type I IFNs and TLR-activated Ly6C hi monocytes (24,26). Nonautoimmune-prone STING-deficient mice do not exhibit any evidence of systemic autoimmunity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…STING-deficient MRL/lpr mice develop a dramatically accelerated disease profile characterized by the expansion and activation of both the lymphoid and myeloid compartments, increased numbers of type I IFN-producing cells, elevated autoantibody titers, and a shorter lifespan. Similar to our findings in the MRL/lpr model, STING deficiency exacerbated TMPD-induced inflammation, a condition also associated with type I IFNs and TLR-activated Ly6C hi monocytes (24,26). Nonautoimmune-prone STING-deficient mice do not exhibit any evidence of systemic autoimmunity.…”
Section: Discussionsupporting
confidence: 88%
“…These features include a type I IFN signature, ANAs, and glomerulonephritis (24,25). Importantly, TMPD-induced autoimmunity is dependent upon TLR7 and type I IFNs (26). Pristane injection of C57/Bl6 mice results in an early and persistent peritoneal inflammation and the recruitment of TLR7 hi Ly6C hi monocytes, a potential source of type I IFNs, in this model (25).…”
Section: Sting Deficiency Results In the Increased Expression Of Ifn-mentioning
confidence: 84%
“…In addition, Christensen, et al [6] showed that lupus nephritis takes a significantly milder course in Tlr7-deficient MRLlpr/lpr mice. This was confirmed in pristane-induced lupus nephritis in C57BL/6 mice [8]. Both studies also observed a significant reduction in the plasma levels of IgG2a/2c isotype antibodies in Tlr7-deficient mice mice [6,8].…”
Section: See Accompanying Article By Fairhurst Et Almentioning
confidence: 53%
“…Both studies also observed a significant reduction in the plasma levels of IgG2a/2c isotype antibodies in Tlr7-deficient mice mice [6,8]. Lack of Tlr7 in MRLlpr/lpr mice was associated with a general reduction in immune activation affecting the proliferation and activation of splenic B and T lymphocytes [6], which was not observed in pristane-induced lupus in C57BL/6 mice [8].…”
Section: See Accompanying Article By Fairhurst Et Almentioning
confidence: 85%
See 1 more Smart Citation